2016
DOI: 10.1002/jwmg.21131
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors influence lesser scaup migration chronology and population monitoring

Abstract: Identifying environmental metrics specific to lesser scaup (Aythya affinis; scaup) spring migration chronology may help inform development of conservation, management and population monitoring. Our objective was to determine how environmental conditions influence spring migration of lesser scaup to assess the effectiveness of the Waterfowl Breeding Population and Habitat Survey in accurately estimating scaup populations. We first compared peak timing of mallard (Anas platyrhynchos) and scaup migration from wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 45 publications
1
47
0
Order By: Relevance
“…Use of the WBPHS data to infer spatial changes in breeding populations of scaup is clearly not appropriate (e.g., Afton and Anderson ; Ross et al ; Barker et al , ) because, as documented (this study, Finger et al ), they are still migrating to their breeding sites during the WBPHS. We detected that nearly half (48.8% of the total migrations) of our marked scaup using the traditional survey area were available to be counted more than once as they migrated north with the WBPHS crew.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Use of the WBPHS data to infer spatial changes in breeding populations of scaup is clearly not appropriate (e.g., Afton and Anderson ; Ross et al ; Barker et al , ) because, as documented (this study, Finger et al ), they are still migrating to their breeding sites during the WBPHS. We detected that nearly half (48.8% of the total migrations) of our marked scaup using the traditional survey area were available to be counted more than once as they migrated north with the WBPHS crew.…”
Section: Discussionmentioning
confidence: 95%
“…One of our goals was to use environmental predictors of date of settling outlined in Finger et al () and determine metrics from this study that could be used in the future to refine WBPHS scaup population estimates. Austin et al (), Mallory et al (), and Finger et al () suggested using weather data to adjust the population estimates of the WBPHS, but we caution against such an approach given the clear biases we detected. Development of models that include metrics such as survey stratum latitude and annual spring environmental conditions might potentially be used to improve scaup breeding population estimates derived from the WBPHS, but independent annual population estimates derived from banding data would be necessary to evaluate such models (Arnold et al , ; Koons et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Finger et al. ). Integrated analyses can be used to reconcile such problems with more accurate data that are collected at fewer locations (Hanks et al.…”
Section: Methodsmentioning
confidence: 99%
“…The WBPHS is not well timed for accurately estimating Lesser Scaup abundance because the birds are still migrating (i.e., moving among strata) during the survey period and also settle in non‐surveyed areas (Finger et al. ).…”
Section: Methodsmentioning
confidence: 99%